TOTAL QUALITY MANAGEMENT IN B.ED COLLEGE - Sivaramakrishan, Priti (International Journal of Research -GRANTHAALAYAH, 2016)
The aim of the present study was to investigate the perception of B.Ed student teachers towards Total Quality Management (TQM) in Teacher Training Colleges. The study aims to evaluate how well the college functions in the transaction of imparting the teaching learning process. The study was conducted on 68 B.Ed student teachers from one of the teacher training colleges of Mumbai University. The data was analyzed using percent mean method. The results of the study showed that most of the dimensions of quality control ranged between 60% to 75% which suggests that the said college has room for improvement on its services.